2001
DOI: 10.1046/j.1469-7580.2001.19810057.x
|View full text |Cite
|
Sign up to set email alerts
|

The structural organisation of sperm head components of the wombat and koala (suborder: Vombatiformes): an enigma amongst marsupials

Abstract: The sperm head structural organisation of the koala and hairy-nosed wombat, and the effects of varying concentrations of the ionic detergent, Triton X-100, on its component parts, were determined by electron microscopy. Although alike in form between the 2 species, the sperm nucleus of the former, but not the latter, had nuclear vacuoles and appeared to be more easily dispersed by the Triton X-100. The structure of the acrosome of the spermatozoon was similar between the 2 species and, in both, previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
(35 reference statements)
1
8
0
Order By: Relevance
“…In some sense, these same sperm domains have also been identified in koalas as 'hot spots' to initiate sperm DNA damage. Breed et al (2001) have noted the presence of a thin segment of the koala acrosome that runs from the main body of the acrosome towards the attachment of the tail and also laterally around the edges of the nucleus; again these areas are consistent with the DNA fragmentation 'hot spots' identified in the current study. Whatever the mechanism of chromatin relaxation, the koala sperm must have its own peculiar chromatin organisation, because relaxation of the chromatin in this species is not as pronounced as in the closely related wombat.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In some sense, these same sperm domains have also been identified in koalas as 'hot spots' to initiate sperm DNA damage. Breed et al (2001) have noted the presence of a thin segment of the koala acrosome that runs from the main body of the acrosome towards the attachment of the tail and also laterally around the edges of the nucleus; again these areas are consistent with the DNA fragmentation 'hot spots' identified in the current study. Whatever the mechanism of chromatin relaxation, the koala sperm must have its own peculiar chromatin organisation, because relaxation of the chromatin in this species is not as pronounced as in the closely related wombat.…”
Section: Discussionsupporting
confidence: 76%
“…The release of chromatin damaging agents such as proteases might be expected from the acrosome, particularly when associated with damaged plasma membranes. Although the marsupial acrosome is generally thought to be resistant to cryoinjury (Sistina et al 1993, Breed et al 2001, Johnston & Holt 2001, this might still be a plausible explanation for co-localisation of initial DNA damage and the peri-acrosomal region in this study. Although the marsupial acrosome is known to be highly stable, even to the repeated effects of a freeze-thaw procedure (Sistina et al 1993), rupture or more subtle damage of the underlying nuclear or acrosomal membranes might still occur in the peri-acrosomal region during cryopreservation.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Hughes (1965) revealed that vombatid spermatozoa were murid-like in morphology and unique amongst the marsupials; the sperm head is 'sickle-shaped' and the neck of the flagellum inserts disto-ventrally. Although the overall sperm head shape of the koala and wombat are similar in form, there are small inter-species differences in the chromatin structural organisation (Breed et al 2001). Nevertheless, both species have an acrosome that lies within the concavity of the nucleus and from this region a thin segment of acrosome runs both posteriorally and laterally (Breed et al 2001).…”
Section: Male Micro-anatomymentioning
confidence: 99%
“…While penile spines in other mammals (e.g. felids) are sometimes associated with vaginal or cervical stimulation resulting in induced ovulation, there is currently Owen (1919) CW _ Detailed account of the gross anatomy of the reproductive system \ Full description of the gross urogenital anatomy Pearson (1944) CW \ Description of the gross urogenital anatomy Barnett & Brazenor (1958) CW _ Presence of a rete mirabile in the spermatic cord Hughes (1965) CW _ Sperm morphology Brooks et al (1978) SHNW _ Full description of the reproductive system; structural and biochemical characteristics of accessory reproductive glands; sperm morphology Barbour (1981) SHNW _ Full description of the reproductive system; histology and histochemistry of accessory reproductive glands Gaughwin (1981) SHNW _ Structural and biochemical characteristics of the reproductive organs \ Structural characteristics of the urogenital tract Hughes & Green (1998) CW \ Placentation Moritz et al (1998) CW \ Ovarian and uterine histological changes associated with the oestrous cycle Taggart et al (1998) SHNW _ Seminal characteristics Hamilton et al (2000) SHNW _ Seasonal change in accessory glands (structure) Breed et al (2001) CW _ Sperm morphology (i.e. the structural organisation of sperm head components) MacCallum (2004) CW _ Gross anatomy and testicular histology of the reproductive tract and sperm morphology \ Examined the urogenital system (i.e.…”
Section: Male Gross Anatomymentioning
confidence: 99%